Variability in the composition of extracellular polymeric substances from a full-scale aerobic granular sludge reactor treating urban wastewater - Oliveira, Ana S. (2020)
Within the framework of the circular economy, there is a need for waste management alternatives that promote the reuse of materials produced in wastewater treatment plants (WWTP). An interesting option is the recovery of extracellular substances from sludge. The variability of characteristics of potential recovered bioproducts has to be assessed in full scale operational settings. In this study, aerobic granular sludge (AGS) from a full-scale WWTP treating urban wastewater was regularly collected for 4 months to assess variability in extracellular polymeric substances (EPS) composition and in granular morphology. Variations in the EPS composition occurred with time. Proteins and humic substances were the main EPS components (329-494 and 259-316?mg/g VSS of AGS, respectively), with polysaccharides and DNA representing minor components. The application of an extra purification step after extraction to obtain a purer EPS led to a decrease in the yield of each EPS component, particularly pronounced for the polysaccharides. The final product had a rather constant composition for the monthly samples. The granules showed morphological stability throughout the sampling period and the yield of EPS was correlated to the size of the granules, higher when there was a higher content of small granules (Deq<150?µm) comparing to intermediate (150???Deq<1500?µm) or large granules (Deq?1500?µm). This is the first time that a potential valorization strategy for surplus AGS biomass is studied in a full-scale environment. Knowledge on yield and product homogeneity is important as these features are essential for downstream application of the recovered EPS.